Professional Standards for the Superintendency - The AASA Commission on Standards for the Superintendency; Hoyle, John R. (Rowman & Littlefield Publishers, 1993)
School superintendents provide leadership and inspiration in school districts across the country. They must be skilled collaborators who can rally resources to support better education for all children living in our multicultural society. Professional standards will help to ensure excellence in the American school superintendency. Developed by a special AASA Commission on Standards for the Superintendency and reviewed by a national 'Jury of 100' business and education leaders, these eight standards combine administrative knowledge with research on performance goals, competencies and skills in the following areas: leadership and district culture; policy and governance; communications and community relations; organizational management; curriculum planning and development; instructional management; human resources management; and the values and ethics of leadership.